ANALISA KADAR CEMARAN MERKURI (Hg) PADA IKAN TUNA (Thunnus sp.) KEMASAN KALENG SECARA SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Adiansyah, Adiansyah; Silalahi, Yosy Cinthya Eriwaty; Ritonga, Ahmad Hafizullah (Jurnal Farmanesia, 2019)
Mercury is a heavy metal that can have a toxic effect on the body so that it can cause death. Mercury metal contamination in food is regulated in SNI number 7387 of 2009 regarding the Maximum Heavy Metal Limit. Some metal waste disposal ends up in river, lake, or sea waters so that metal pollution can occur in the ecosystem. This study aims to determine the levels of mercury metal contamination in canned tuna. Sample preparation was carried out using the wet digestion method with a microwave digestion device. The results of the analysis showed that from the six samples of canned tuna fish according to the maximum limit and meet the standard maximum limit of 1.0 mg/kg SNI. Mercury analysis was carried out using the AAS (Atomic Absorption Spectrophotometry) method. The wavelength used is at 253.7 nm. The results showed that the mercury in tuna brand A was 0.9030±0 mg/kg tuna brand B 0.1029±0 mg/kg, tuna brand C 0.4524±0 mg/kg, tuna brand C D 0.0967±0 mg/kg, tuna brand E 0.9567 ± 0 mg/kg, and tuna brand F 0.8034±0 mg/kg.